Penerapan Standar Operasional Prosedur Pengadaan Bahan Pustaka di Perpustakaan Institut Teknologi Padang - Hakim, Lukmannul; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed on Standard Operating Procedures of procurement of library materials in the Library of the Institute of Technology Padang. This study aims to (1) describe the SOP procurement of library materials in the Library of the Institute of Technology Padang, (2) mendiskripskan constraints found in the application of SOP procurement of library materials at the Institute of Technology Padang, and (3) describe efforts to overcome obstacles in the implementation of SOP procurement of library materials in the library of the Institute of Technology Padang. This research uses descriptive method. ie the data collected through observation, interviews, and study documents in the Library of the Institute of Technology Padang (ITP). Based on the results of this study concluded the following things; First, the application of SOP procurement of library materials in the Library Technology Institus Padang has not done well. Second, the obstacles encountered in the implementation of SOP as follows: (1) some employees have not implemented the SOP in ITP Library; (2) the existence of human error. Third, efforts are being made to overcome the obstacles, namely: (1) the library should seek the presence of a sosiolisasikan SOP procurement of library materials to officers who do not know the SOP in the Library ITP (2) human error due to feeling bored and not in the spirit.Keyword: standar operasional prosedur, pengadaan, bahan pustaka